SELOKO ADAT MELAYU JAMBI: REFLEKSI KEARIFAN LOKAL DALAM TRADISI DAN BUDAYA MASYARAKAT MELAYU JAMBI - Dina Chabib Uluum; Hanan Riswar; yogia prihartini; Musli; Mustar; Muhamad Khumaini Umasugi (Rihlah : Jurnal Sejarah dan Kebudayaan, 2025)
Seloko Adat Melayu Jambi is one of the oral literatures that is an inseparable part of the local wisdom of the Malay Jambi community. This tradition contains cultural, moral, and social values ​​that are passed down from generation to generation. This study aims to examine the role of Seloko Adat in shaping the cultural identity of the Malay Jambi community, as well as how this tradition functions as a guideline for life in facing social dynamics and modernization. With a qualitative approach, this study reveals that Seloko Adat is not only a tool for cultural communication, but also functions as a conflict resolution mechanism, a strengthener of harmonious values, and a guardian of customary norms, as well as a reminder of religious rules. Viewed from an anthropological perspective which includes normative studies, empirical studies, scientific studies, and analysis of interconnected integration. Seloko Adat Melayu Jambi merupakan salah satu sastra lisan yang menjadi bagian tidak terpisahkan dari kearifan lokal masyarakat Melayu Jambi. Tradisi ini memuat nilai-nilai budaya, moral, dan sosial yang diwariskan secara turun-temurun. Penelitian ini bertujuan untuk mengkaji peran Seloko Adat dalam membentuk identitas budaya masyarakat Melayu Jambi, serta bagaimana tradisi ini berfungsi sebagai pedoman hidup dalam menghadapi dinamika sosial dan modernisasi. Dengan pendekatan kualitatif, penelitian ini mengungkapkan bahwa Seloko Adat tidak hanya menjadi alat komunikasi budaya, tetapi juga berfungsi sebagai mekanisme resolusi konflik, penguat nilai-nilai harmoni, dan penjaga norma adat, serta pengingat dari aturan agama. Dilihat dari segi antropologi yang didalamnya mencakup kajian normatif, kajian empirik, kajian saintifik, dan analisis integrasi interkoneksi.